Knowledge about the disease and adherence to treatment in patients with Diabetes - Loeser Corazza, André Luiz; Faggion Schramm, Patrícia; Zapola da Silva, Amanda; Correa Cardoso, Thiago; Matos de Castro, Rodrigo; Vaz Machry, Rafael (Clinical and Biomedical Research, 2023)
INTRODUCTION: Glycemic decompensation in is one of the major factors for the development of chronic disease complications. Factors involved in the adequate control of diabetes include adherence to pharmacological treatment and knowledge about the disease. METHODS: Cross-sectional study on the factors associated with adherence to drug treatment and knowledge about diabetes in diabetic patients treated at Hospital Universitário de Santa Maria between 2018 and 2019, based on the validated Morisky-Green test and on the Diabetes Knowledge Questionnaire. RESULTS: A total of 201 patients diagnosed with diabetes were included, the majority (85.6%) of which had type 2 diabetes and were white (75.6%), with a mean age of 59.4 years. An association between insufficient knowledge about diabetes and patients with type 2 diabetes was observed. An association was found between patients with type 2 diabetes using insulin and non-adherence to drug treatment compared with patients with type 2 diabetes who did use insulin. The research also showed that non-adherence to drug treatment was associated with higher occurrence of hypoglycemia compared with patients who adhered to drug treatment. CONCLUSION: The data obtained in our study allows us to conclude that non-adherence to pharmacological treatment makes diabetes therapy more complicated and worsens the prognosis.